KARAKTER MANDIRI PESERTA DIDIK SD SWASTA SULUH HARAPAN SINTANG MASA PANDEMI COVID 19 - Daniel Dike; Sirilus Sirhi; Risa Natalia (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
The purpose of this study was to provide an overview of how the character formation of the Suluh Harapan Private Elementary School students during learning during the covid 19 pandemic. This study used a qualitative descriptive study, by examining the character formation of students, teachers, parents and school principals through interviews. , and documentation. The results of this study indicate that the strengthening of students' independent character emerges from the results of the integration of school principals in fulfilling online learning infrastructure, teacher integration in developing interesting learning, one of which is by giving craft assignments to be used as learning materials applied in both offline and bold learning, the integration of students to help increase curiosity and active learning, one of which is interesting, one of which is the handicrafts provided by the Suluh Harapan Sintang Private Elementary School teacher, as well as the integration of students' parents who help and monitor the use media during home learning.